AN ANALYSIS OF VERTICAL DEFORMATION ON CIANJUR EARTHQUAKE 2022 - Nurlukman, Candra Perkasa; Wibowo, Adi (UI Scholars Hub, 2025)
A shallow crustal-type earthquake on a surface fault occurred on November 21, 2022, in Cianjur, West Java. This destructive earthquake resulted in a loss of life, many houses were damaged, and landslides at several points. So, the research was analyzed using the DInSAR method to see the deformation and its relationship with the existing conditions in the field. We get the result of a vertical subsidence in the earthquake area of up to 101 millimeters. Through the distribution of displacement results, we found no overlapping faults at that location, identifying the formation of a new fault. In the distribution area of land subsidence, which overlaps with the location of the landslide occurrence, we also analyze the relationship between soil type and elevation, which may be related. With the data on affected buildings from BNPB, we analyze that around 44.4% of the total lightly damaged houses, 31.1% of the total moderately damaged houses, and 24.5% of the total heavily damaged houses are in the displacement distribution. Many factors cause damage to homes, but in this case, we can conclude that DInSAR analysis can see the deformation of the earth's surface.